Analyzing Multi-Actor Communication Pathways In Higher Education Choice Among Islamic Senior High School Students In Malang, Indonesia - Ali, Ahmad Nabil; Wulandari, Maulina Pia; Prasetyo, Bambang Dwi (INJECT (Interdisciplinary Journal of Communication), 2026)
Higher education choice is not merely an individual decision based on academic interest or institutional promotion, but a socially negotiated process involving parents, school counselors, and peers as important reference groups. However, existing studies on university choice often emphasize individual rational choice and marketing persuasion, while paying limited attention to how reference groups shape legitimacy and final decision-making. This study examines how Islamic senior high school students in Malang City communicate and negotiate with their key reference groups during the higher education selection process. Using a qualitative approach, data were collected through focus group discussions with 10 final-year students, complemented by semi-structured interviews involving 2 guidance and counseling teachers from two Islamic senior high schools with contrasting institutional and socioeconomic backgrounds, and 1 external tutoring teacher to enrich the data. The data were analyzed thematically with the assistance of NVivo. The findings produce the Multi-Actor Iterative Communication (MAIC) Model of University Choice, reframing recruitment not as a linear marketing funnel, but as a circular, recursive communication system. The model concludes that prospective students' choices only solidify into enrollment when marketing stimuli successfully align personal aspirations with parental validation, data-driven school guidance, performance analytics from external tutors, and horizontal peer exploration. Ultimately, this study provides higher education marketers with a novel marketing framework to strategically navigate a distributed network of community gatekeepers rather than targeting isolated consumers.